1925 N.D. Laws 216-17 - (:unkn) unknown (My University, 1925)
Ch. 174, § 2: Committing Crime When Armed. If any person shall commit, or attempt to commit, a crime when armed with a pistol or revolver, and has no permit to carry the same, he may be punished by imprisonment for not more than ten years, in addition to the punishment provided for the crime. Such imprisonment, if not exceeding one year, to be in the County jail, and if exceeding one year to be in the State Penitentiary.
Keywords: COMMITTING CRIME W/ WEAPON